2010
DOI: 10.1007/s11357-010-9145-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term recognition memory impairment is associated with decreased expression of FK506 binding protein 51 in the aged mouse brain

Abstract: Evidence suggests that increased glucocorticoid receptor (GR) signaling may contribute to cognitive decline with age. We hypothesized that alterations in GR signaling pathway molecules, FK506 binding protein (FKBP) 51 and FKBP52, were associated with memory impairment in aged mice. We used the single-trial object recognition test to measure short-term memory in 18 aged mice compared to 22 young mice, and employed quantitative immunohistochemistry to assess cellular expression of those three proteins in the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Research has shown Fkbp5 gene expression in the adult brain [24,55] and in mice as young as three months [56]. The current study revealed Fkbp5 expression in the brain of one-month-old mice.…”
Section: Discussionsupporting
confidence: 55%
“…Research has shown Fkbp5 gene expression in the adult brain [24,55] and in mice as young as three months [56]. The current study revealed Fkbp5 expression in the brain of one-month-old mice.…”
Section: Discussionsupporting
confidence: 55%
“…These markers were quantified in frontal cortex, frontal white matter, hippocampus, and putamen. Histopathology and quantification procedures for these were described previously(Soontornniyomkij et al, 2010; Soontornniyomkij, Soontornniyomkij, et al, 2012; Toggas & Mucke, 1996). No correlations between age acceleration and any marker in any region were observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoperoxidase staining was performed on nine of the METH-exposed mice. Staining was done on 5μm-thick paraffin-embedded paraformaldehyde-fixed coronal brain sections with anti-calbindin-1 antibody (#AB1778, Millipore, Billerica, MA, USA, 1:300 dilution) and anti-DAT (6-5G10, #sc-3258, Santa Cruz Biotechnology, Santa Cruz, CA, USA, 1:100), as described previously (Soontornniyomkij et al, 2010). The immunostained slides were digitally scanned (Aperio ScanScope GL, Vista, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The immunostained slides were digitally scanned (Aperio ScanScope GL, Vista, CA, USA). The immunoreactivity intensity was measured within (Image-Pro Analyzer software, Version 6.3, Media Cybernetics, Bethesda, MD, USA) and normalized to the anatomic area, i.e., the combined hippocampal CA1 strata oriens, pyramidale, radiatum, and lacunosum-moleculare for calbindin-1; and the caudate-putamen for DAT, as previously described (Soontornniyomkij et al, 2010). …”
Section: Methodsmentioning
confidence: 99%